2022
DOI: 10.22246/jikm.2022.43.3.363
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Effectiveness and Safety of <italic>Banhasasim-tang</italic>, <italic>Gumiganghwal-tang</italic>, or <italic>Pyeongwee-san</italic> in Patients with Type 2 Diabetes Mellitus

Abstract: Objective: This study was conducted to evaluate the hypoglycemic effect and safety of herbal extracts in patients with type 2 diabetes mellitus.Methods: We investigated 19 hospitalized patients with type 2 diabetes mellitus who were administered <i>Banhasasim-tang</i> (BST), <i>Gumiganghwal-tang</i> (GGT), or <i>Pyeongwee-san</i> (PWS) at Kyung Hee University Korean Medical Hospital for at least three days between January 2012 and December 2021. Their clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The 1-13 compounds from the n-BuOH fraction were isolated by bioassay-guided isolation method and identified structure. As a result, the compounds were determined two carboxylic acids (1,6), one furan derivative (2), and ten phenolics (3)(4)(5)(7)(8)(9)(10)(11)(12)(13). The identified compounds were levulinic acid (1), 5-hydroxymethylfurfural (5-HMF) (2) protocatechuic acid (3), protocatechuic aldehyde (4), 4-hydroxybenzoic acid (4-HBA) (5), benzoic acid (6), vanillic acid (7), 5-O-caffeoylquinic acid (5-O-CQA) (8), chlorogenic acid (9), caffeic acid (10), syringic acid (11), 3,5-Di-O-caffeoylquinic acid (3,5-Di-O-CQA) (12), and 3,4-Di-O-caffeoylquinic acid (3,4-Di-O-CQA) (13).…”
Section: Identification Of Isolated Compounds From a Lancea Water Ext...mentioning
confidence: 99%
See 1 more Smart Citation
“…The 1-13 compounds from the n-BuOH fraction were isolated by bioassay-guided isolation method and identified structure. As a result, the compounds were determined two carboxylic acids (1,6), one furan derivative (2), and ten phenolics (3)(4)(5)(7)(8)(9)(10)(11)(12)(13). The identified compounds were levulinic acid (1), 5-hydroxymethylfurfural (5-HMF) (2) protocatechuic acid (3), protocatechuic aldehyde (4), 4-hydroxybenzoic acid (4-HBA) (5), benzoic acid (6), vanillic acid (7), 5-O-caffeoylquinic acid (5-O-CQA) (8), chlorogenic acid (9), caffeic acid (10), syringic acid (11), 3,5-Di-O-caffeoylquinic acid (3,5-Di-O-CQA) (12), and 3,4-Di-O-caffeoylquinic acid (3,4-Di-O-CQA) (13).…”
Section: Identification Of Isolated Compounds From a Lancea Water Ext...mentioning
confidence: 99%
“…1 AR has been valued as a traditional herbal medicine (THM) in East Asia for centuries. 24 It is believed to have various bioactivities and is commonly used to treat gastrointestinal and digestive disorders. 5 Recent studies have also demonstrated that the extract from A. lancea exhibits anticancer, hepatoprotective, anti-diabetic, and antiinflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…한약을 병용 투약했을 때 혈당에 미치는 영향 및 안전성을 보고한 기존 연구를 살펴보면, 한약 처방이나 한약재의 종류가 명시되어 있지 않거나 4 다빈도로 처방되는 의료보험용 한약제제 중 소수 5,6 에 대해서만 보고된 바 있어, 기타 다른 한약에 대 한 병행 치료의 안전성에 대한 연구는 미미한 실 정이다. 보중익기탕은 건강보험심사평가원에서 의 료보험용 혼합엑기스제제로 지정한 56종의 한약제 제에 해당하며, 2017년부터 2021년까지 꾸준히 청 구건수 10위 내에 해당하는 다빈도 처방 약물로 7 , 일반적으로 허약체질, 피로권태, 식욕감퇴 등의 증 상에 효과가 있다고 알려져 있으며 8 중국에서는 혈 당 강하 효과도 보고된 바 있다 9 .…”
unclassified